Description of a new Peronia species (Gastropoda: Eupulmonata: Onchidiidae) from Iran, Persian Gulf - Maniei, Fatemeh; Espeland, Marianne; Movahedi, Mohammad; Wägele, Heike (Zootaxa, 2020)
Peronia J. Fleming, 1822 is an eupulmonate slug genus with a wide distribution in the Indo-Pacific Ocean. Currently, nine species are considered as valid. However, molecular data indicate cryptic speciation and more species involved. Here, we present results on a new species found in the Persian Gulf, a subtropical region with harsh conditions such as elevated salinity and high temperature compared to the Indian Ocean. Peronia persiae sp. nov. is described based on molecular, histological, anatomical, micro-computer tomography and scanning electron microscopy data. ABGD, GMYC and bPTP analyses based on 16S rDNA and cytochrome oxidase I (COI) sequences of Peronia confirm the delimitation of the new species. Moreover, our 14 specimens were carefully compared with available information of other described Peronia species. Peronia persiae sp. nov. is distinct in a combination of characters, including differences in the genital (ampulla, prostate, penial hooks, penial needle) and digestive systems (lack of pharyngeal wall teeth, tooth shape in radula, intestine of type II).